Dynamics of molecular parameters of human immunodeficiency virus type 1 activity in vivo. - Bagnarelli, P (1994)
The dynamics of viral activity during different phases of human immunodeficiency virus type 1 (HIV-1) infection were investigated by competitive PCR methods. In particular, we studied the time course of three quantitative molecular parameters of viral activity (genomic RNA copy number in plasma and provirus and late HIV-1 transcript molecule copy numbers in peripheral blood CD4+ T lymphocytes) in untreated patients and patients treated with specific anti-HIV-1 compounds. The results shown here indicate that direct RNA parameters are quantitative molecular indices sensitive enough to be used for a more accurate evaluation of the natural history of this infection and that an indirect parameter, the mean transcriptional activity for each provirus in CD4+ T lymphocytes, may be important in studying this infection in vivo at the molecular level. A dramatic decrease of the indices was evident at seroconversion, but the quantitative values were virtually stable throughout the time the untreated patients were studied during the clinical latency phase. Furthermore, the results indicate that an early response to antiretroviral compounds is detected in most subjects as a decrease in the viral activity level.